Analysis of Sway in ballroom dancing - Shioya, T. (Proceedings, 2018)
According to syllabi of ballroom dancing, the sway is explained as the inclination of the body towards the inside of the turn. This explanation is questionable and a more adequate explanation is given based on a mechanical analysis with a new concept of inclination and bending sways. First, the sway mechanism is explained as the balance of the inertia force and the inclination using one-element model. Further a two-element model is introduced including both the inclination and the bending effects. The model explains the control and stability of sway. The sway process is classified into three stages, and the change of the inclination and bending with time is demonstrated by the analysis. The understanding of sway mechanism improves the dancers' swing movements.